2020
DOI: 10.15296/ijwhr.2022.06
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of General Anesthesia With Spinal Anesthesia on the Quality of Recovery of Patients With Selective Abdominal Hysterectomy in Patients Vising the Largest Women’s Disease Hospital in Northwestern Iran

Abstract: Objectives: The quality of recovery can affect the results of abdominal hysterectomy although this effect is unknown in different methods of anesthesia. Therefore, the present study was conducted to compare general anesthesia (GA) and spinal anesthesia (SA) methods on the quality of the recovery of patients with selective abdominal hysterectomy in patients visiting the largest women’s disease hospital in Northwestern Iran. Materials and Methods: This cross-sectional descriptive study was conducted with the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
2
1
Order By: Relevance
“…In this regard, the results of similar studies reported no significant differences between the SPA and GA groups in terms of nausea There was no significant difference between the two groups in terms of recovery time, nausea and vomiting which confirms the results of the present study. On the other hand, some previous studies were not in accordance with the results of this study, and showed that the frequency of nausea/vomiting was greater in the GA group compared to the SPA group (18,41). Most of the drugs used in GA can cause nausea and vomiting, but this difference can be due to the use of propofol in induction of anesthesia in the present study.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…In this regard, the results of similar studies reported no significant differences between the SPA and GA groups in terms of nausea There was no significant difference between the two groups in terms of recovery time, nausea and vomiting which confirms the results of the present study. On the other hand, some previous studies were not in accordance with the results of this study, and showed that the frequency of nausea/vomiting was greater in the GA group compared to the SPA group (18,41). Most of the drugs used in GA can cause nausea and vomiting, but this difference can be due to the use of propofol in induction of anesthesia in the present study.…”
Section: Discussioncontrasting
confidence: 94%
“…Most of the drugs used in GA can cause nausea and vomiting, but this difference can be due to the use of propofol in induction of anesthesia in the present study. Nausea and vomiting in surgeries (e.g., hysterectomy) can put pressure on the intestine and the lower gastrointestinal tract, which can have adverse effects on the results of hysterectomy (41). Therefore, the type of anesthesia method should be considered by anesthesiologists to minimize nausea and vomiting.…”
Section: Discussionmentioning
confidence: 99%
“…Spinal anaesthesia (SA), so called spinal block, is one of the most prevalent types of anaesthetic procedures, sometimes being superior to the general anaesthesia (Yüksek et al, 2020). In several comparable studies, SA had some superiority to the general anaesthesia (GA) in safety and in possible procedure-related complications (Visser et al, 2009;Mortazavi et al, 2022). Because of prevalent usage of this technique, knowing possible complications and pitfalls are crucial.…”
Section: Introductionmentioning
confidence: 99%